Temporal and Spatial Assessment of Usable Space and Cover Type Interspersion for Northern Bobwhites on Private Farmlands in Southwestern Ohio - Robert J. Gates; Mark J. Wiley; Adam K. Janke; Marjorie R. Liberati (National Quail Symposium Proceedings, 2017)
Contemporary landscape change driven by socio-economic forces and advances in agricultural technology do not favor northern bobwhites (Colinus virginianus) in the Midwestern United States. The challenge of bobwhite conservation is to provide sufficient quantities of habitat with optimal configurations in proportions that satisfy needs throughout the year on private-owned working lands. We radio-tracked 58 coveys and 98 individual birds throughout the year in 2009-10 and 2010-11 on privately owned farmland in southwestern Ohio. We investigated temporal changes in usable space from use-availability data. Estimated proportions of usable space based on analyses of habitat selection across four study sites were 0.06-0.12 during the non-breeding season compared to 0.10-10.30 during the breeding season. We also modeled probabilities that radio-marked coveys or individual birds used points within individual cover types as a function of distance to other cover types. Locations of radio-marked coveys and individual birds within focal cover types were closer to other cover types compared to random points during breeding (mean = 44 m) and non-breeding (mean = 58 m) seasons. Probability of use within focal cover types declined with distance to other cover types, typically falling below 50% when distances exceeded 9-242 m. Locations of radio-marked coveys were concentrated near edges within used cover types, while locations of individual birds were more dispersed during the breeding season. Estimated proportions of usable space based on distances between locations of radio-marked bobwhites and nearest cover types were higher (0.30-0.53) than estimates based on habitat selection ratios, and were similar between non-breeding and breeding seasons. Potentially usable sites were not fully occupied in either season, but there was no relationship between crude covey densities and proportions of usable space estimated from habitat selection analyses during the breeding and non-breeding seasons across study sites and years (r2 < 0.166, P > 0.316). With distance to cover type estimates of usable space (years combined), two study sites with the highest proportions of usable space (0.43-0.53) also had the largest crude covey densities (0.0065-0.153 coveys/ha) compared to the other two sites with lower proportions of usable space (0.30-0.32) and smaller covey densities (0.004 – 0.006 coveys/ha). Habitat enhancement should focus on providing protective cover near food for coveys during the non-breeding season and protective cover near nesting and brood-rearing habitat during the breeding season. Conserving Midwestern bobwhite populations requires innovative practices that can be implemented on private lands as economic incentives change for farm operators. Improving protective cover along habitat edges can increase usable space by improving cover type juxtaposition (e.g. food near cover) while minimizing impact on farming practices.
Keywords: Colinus virginianus; northern bobwhite; habitat use; interspersion; Ohio; private lands; quail; radio-telemetry; usable space